Immunogenicity of recombinant HS ABA392 DNA vaccine against Haemorrhagic septicaemia in animal model / Shamini Chelliah - Shamini , Chelliah (2018)
Pasteurella multocida is the main cause of haemorrhagic septicaemia (HS) outbreak in livestock, such as cattle and buffaloes. This disease is caused by P. multocida serotype B (PMB) (strain 202), a gram-negative bacterial pathogen associated with a variety of disease in domestic animals. The acute form of HS is manifested by sudden onset and death within 24 hours. In Malaysia, HS outbreak has caused an average of 360 heads of cattle and buffaloes killed in a year. Conventional vaccines such as alum-precipitated or oil-adjuvant broth bacterins were injected subcutaneously to provide protection against HS. However, the immunity developed is only short-term and needed to be administered frequently. In previous study, a short gene fragment from P. multocida serotype B:2 were obtained via shotgun cloning technique and later were cloned into bacterial expression system. pQE32-ABA392 was found to possess immunogenic activity towards HS when tested in vivo in rat model. In this study, the targeted gene fragment of ABA392 was sub-cloned into a DNA expression vector pVAX1 and named as pVAX1-ABA392. The new recombinant vaccine was stable and expressed via intramuscular. Serum sample collected from a group of vaccinated rats for ELISA test shows, that the antibody in immunized rats was presence in high titer and can be tested as a vaccine candidate with challenge in further studies. Total white blood count shows leukocytosis. The RFT and LFT were in normal values in the vaccinated group. This successful recombinant vaccine is immunogenic and potentially could be used as vaccine in future against HS.